Complexity and polyadenylic acid content of visna virus 60-70S RNA. - Vigne, R (1977)
The genomic complexity of visna virus was measured by quantitative analysis of 18 RNase T1-resistant oligonucleotides from 60-70S RNA. T1-resistant oligonucleotides were separated by two-dimensional polyacrylamide gel electrophoresis. Visna virus had a genomic complexity of 3.6 X 10(6) daltons, very close to the size of a single 30-40S RNA subunit. It was therefore concluded that the visna virus genome is largely polyploid. Visna virus 60-70S RNA polyadenylic acid segment was purified by T1 RNase digestion followed by oligodeoxythymidylic acid-cellulose column chromatography. It contained over 99% AMP and had a size of about 200 nucleotides. The binding capacities on oligodeoxythymidylic acid-cellulose of native 60-70S RNA and purified 30-40S RNA subunits were examined. It was concluded that two out of three intact subunits contain a polyadenylic acid segment.